Peran Filsafat Pendidikan dalam Perkembangan Kritisitas dan Kreatvitas Siswa - Sania Mutia Salsabila; Sobrun Jamil; Jelita Ayi Widiarti; Alifyani Azzahroh (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
Educational philosophy plays a significant role in developing students’ thinking abilities, especially in improving critical thinking competence and creativity. Through learning strategies that encourage students to actively ask questions, analyze, and evaluate information, students can develop into more rational, critical, and independent individuals in making decisions. This study aims to explore the role of educational philosophy in developing students’ critical reasoning competence and creativity. The research employed a qualitative method using a literature study approach. Data were obtained from various sources, including books, scientific journals, and articles relevant to the research topic. The findings show that the implementation of educational philosophy through discussions, question-and-answer methods, and experience-based learning (learning by doing) can improve students’ analytical skills while encouraging the emergence of creative and innovative ideas. In addition, a learning environment that provides students with opportunities to express their opinions can support the optimal development of their potential. Thus, educational philosophy not only functions as a theoretical foundation in education but also has practical applications in creating creative, active, and progressive learning environments. Therefore, the implementation of educational philosophy is important in producing a generation that is creative, analytical, and capable of facing the challenges of the modern era.